2013
DOI: 10.1542/peds.2013-0511
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum and Intrapartum Factors Preceding Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Etiology and timing of onset of neonatal hypoxic-ischemic encephalopathy continue to be controversial. Previous studies suggest antepartum events are the main contributing factors, but have used a broad definition of encephalopathy and included infants with genetic, congenital, and developmental abnormalities.WHAT THIS STUDY ADDS: Our study suggests that when strict criteria defining hypoxic-ischemic encephalopathy are applied with supporting neuroimaging evidence of an acute hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 46 publications
(58 reference statements)
4
84
2
4
Order By: Relevance
“…We have to take into consideration the difficulty of applying a preventative measure at the exact time of injury in a clinical setting. Nevertheless, although formal randomized clinical trials have not been performed on this drug, its safety profile is high (5, 26), so we can envision a scenario where MB is used as a therapeutic option in cases with a high risk of developing perinatal asphyxia (6,33).…”
Section: Discussionmentioning
confidence: 99%
“…We have to take into consideration the difficulty of applying a preventative measure at the exact time of injury in a clinical setting. Nevertheless, although formal randomized clinical trials have not been performed on this drug, its safety profile is high (5, 26), so we can envision a scenario where MB is used as a therapeutic option in cases with a high risk of developing perinatal asphyxia (6,33).…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite this significant association between fetal Doppler and the need for neonatal unit admission at term, its predictive accuracy as an isolated marker is likely to be poor because of the confounding effect of the process of labor and birth. 27 Whether fetal Doppler assessment in AGA pregnancies is predictive of perinatal morbidity or neurodevelopmental delay is unknown. The extent to which fetal hemodynamic assessment could be used to optimize the timing of delivery and reduce neurodevelopmental impairment merits further investigation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Clinical studies have identified a number of other important antepartum and intrapartum risk factors for neonatal encephalopathy. [7][8][9][10] In low-income settings, where access to skilled birth attendants and emergency obstetric intervention is often limited, the probability of intrapartum hypoxic events contributing to neonatal encephalopathy is increased. 2,9,11 However, in general, neonatal encephalopathy is likely to be a multifactorial condition with complex aetiology, encompassing several causal events, with strong evidence that fetal exposure to infection contributes.…”
Section: Perinatal Brain Injury In the Term-born Infantmentioning
confidence: 99%